Transformational Leadership in Enhancing Teacher Motivation and Skills in Border Areas within the Digital Era - Marinu Waruwu; Rody Putra Sartika; Fatmawati Fatmawati; Eviana Eviana (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2026)
Transformational leadership is an important factor in facing educational challenges in the digital age, which demands innovation, collaboration, and improved teacher competence. This study aims to analyze the role of transformational leadership in improving teacher motivation and skills in Border Areas in the digital era. The research subjects include teachers and principals of senior high schools in the Indonesia-Malaysia border region. The approach used is a mixed method, which is a combination of quantitative and qualitative methods. Data were collected through questionnaires to obtain a quantitative picture of teachers' perceptions of principal leadership, and interviews to explore a more comprehensive understanding of transformational leadership practices in schools. Data analysis was performed using descriptive statistical techniques and thematic analysis. The results of the study show that transformational leadership plays a significant role in increasing teacher work motivation, strengthening professional commitment, and encouraging the development of digital skills relevant to the demands of 21st-century learning. Principals who apply a transformational leadership style are able to create a work environment that is inspiring and adaptive to technological changes. This study recommends the need for digital leadership training programs for principals to strengthen their ability to motivate and empower teachers in the era of educational transformation